2015
DOI: 10.1002/aic.14979
|View full text |Cite
|
Sign up to set email alerts
|

Drop printing of pharmaceuticals: Effect of molecular weight on PEG coated‐naproxen/PEG 3350 solid dispersions

Abstract: Solid dispersions have been used to enhance the bioavailability of poorly water-soluble active pharmaceutical ingredients (APIs). However, the solid state phase, compositional uniformity, and scale-up problems are issues that need to be addressed. To allow for highly controllable products, the Drop Printing (DP) technique can provide precise dosages and predictable compositional uniformity of APIs in two/three dimensional structures. In this study, DP was used to prepare naproxen (NAP)/polyethylene glycol 3350… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Different materials have been printed by inkjet systems spanning from cells to genes or proteins to polymers to nanomaterials and some pharmaceutical formulations …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different materials have been printed by inkjet systems spanning from cells to genes or proteins to polymers to nanomaterials and some pharmaceutical formulations …”
Section: Introductionmentioning
confidence: 99%
“…Different materials have been printed by inkjet systems spanning from cells [10] to genes [11,12] or proteins [13] to polymers [14] to nanomaterials and some pharmaceutical formulations. [15][16][17] In a singular and pioneering work by Hauschild et al, [15] unilamellar nanovesicles were printed from a conventional desktop inkjet printer, using ethanol solutions of both lipidlike and amphiphilic copolymers, resulting in NPs with reproducible sizes ranging between 50 and 220 nm. In the same work, it was also shown that fluorescein-loaded vesicles with narrow-size distributions could be directly produced via the printing method.…”
Section: Introductionmentioning
confidence: 99%
“…Varan et al has investigated the prolonged release behaviour of inkjet printed paxitaxel in a cyclodextrin inclusion complex and cidofovir encapsulated in polycaprolactone nanoparticles dispensed onto bioadhesive films . Low melting temperature PEG/naproxen mixtures Zhu et al, 2013;Hsu et al, 2015) have been reported for melt based inkjet applications in which crystalline domains of the drug could be affected by PEG coatings (Hsu et al, 2015), or controlled melt cooling . Lee et al successfully produced paxlitaxel loaded poly(lactic-co-glycolic acid) microparticles with various geometries (honeycombs, grids, rings and circles) and observed that the drug release rate was dependant on the surface area of the microparticles (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The device achieved zero-order drug release kinetics of antiepileptic drugs, improved patient compliance, achieved effective therapeutic doses, and minimized side effects. In addition, Hsu et al confirmed that the 3D printing technology could produce highly reliable solid dispersions with precise dosage control of active pharmaceutical ingredients [ 181 ]. The study used PEG with an excellent biodegradation profile and naproxen, an anti-inflammatory agent, as a model drug and successfully developed a drug delivery system with uniform composition and sustained-release kinetics.…”
Section: Drug Delivery Systemmentioning
confidence: 99%